Development of a Miller cycle engine with single-stage boosting and cooled external exhaust gas recirculation - He, Yongsheng; Liu, Jim; Zhu, Bin; Sun, David (Proceedings of the Institution of Mechanical Engineers. Part D, Journal of automobile engineering)
In this paper, the development of a Miller cycle gasoline engine which has a high compression ratio from 11.5:1 to 12.5:1, single-stage turbocharging and external cooled exhaust gas recirculation is described. The improvement in the fuel economy by adding external cooled exhaust gas recirculation to the Miller cycle engine at different geometric compression ratios were experimentally evaluated in part-load operating conditions. The potential of adding external cooled exhaust gas recirculation in full-load conditions to mitigate pre-ignition in order to allow higher geometric compression ratios to be utilized was also assessed. An average of 3.2% additional improvement in the fuel economy was achieved by adding external cooled exhaust gas recirculation to the Miller cycle engine at a geometric compression ratio of 11.5:1. It was also demonstrated that the fuel consumption of the engine with external cooled exhaust gas recirculation was reduced by 3–7% in a wide range of part-load operating conditions and that the engine output of the Miller cycle engine at a geometric compression ratio of 12.5:1 increased at 2000 r/min in the full-load condition. The Miller cycle engine with external cooled exhaust gas recirculation at a geometric compression ratio of 12.5:1 achieved a broad brake specific fuel consumption range of 220 g/kW h or lower, with the lowest brake specific fuel consumption of 215 g/kW h. While there are still challenges in implementing external cooled exhaust gas recirculation, the Miller cycle engine with single-stage turbocharging and external cooled exhaust gas recirculation showed its potential for substantial improvement in the fuel economy as one of the technical pathways to meet future requirements in reducing carbon dioxide emissions.